The Use of Titanium in the Friction Units of Artificial Joints - Sheykin, S.Ye.; Pohreliuk, I.M.; Iefrosinin, D.V.; Rostotskiy, I.Yu.; Sergach, D.A. (Science and Innovation, 2024)
The possibility of using titanium in the friction units of artificial joints has been studied. Tribological characteristics of the titanium–Chirulen friction pair have been discussed. A technique for diamond-abrasive machining, polishing, and gas-phase thermal nitridation of spherical heads of pure titanium implants for hip joint endoprostheses has been developed. It is proved the increases of titanium head hardness achieved by pre-grinding the surface layer structure after cold plastic deformation.